Предмет: Алгебра,
автор: ололошка436
решите уравнение (x-2)(x2+6x+9)=6(x+3)
Ответы
Автор ответа:
0
Постав лутшу відповіть пж
(x-1)(x²+6x+9)=5(x+3)
(x-1)(x+3)²-5(x+3)=0
(x+3)((x-1)(x+3)-5)=0
(x+3)(x²+2x-3-5)=0
(x+3)(x²+2x-8)=0
(x+3)(x-2)(x+4)=0 (по теореме Виета устно найдены корни 2 и -4)
x+3=0 v x-2=0 v x+4=0
x₁=-3; x₂=2; x₃=-4
(x-1)(x²+6x+9)=5(x+3)
(x-1)(x+3)²-5(x+3)=0
(x+3)((x-1)(x+3)-5)=0
(x+3)(x²+2x-3-5)=0
(x+3)(x²+2x-8)=0
(x+3)(x-2)(x+4)=0 (по теореме Виета устно найдены корни 2 и -4)
x+3=0 v x-2=0 v x+4=0
x₁=-3; x₂=2; x₃=-4
Похожие вопросы
Предмет: Русский язык,
автор: Iogan123
Предмет: Другие предметы,
автор: mamontchebylash
Предмет: Алгебра,
автор: kewik440
Предмет: Алгебра,
автор: danaalisherkizi
Предмет: География,
автор: yjfhxb